Work of art, museum trophy, memorial monument the Ny Carlsberg Glyptotek's Gloria Victis by Antonin Mercié - Parkinson, Nick (2022)
When museum director Carl Jacobsen installed Antonin Mercié’s sculptural group Gloria Victis (Glory to the Vanquished) in Copenhagen’s Ny Carlsberg Glyptotek in 1906, he made it the centerpiece of the museum’s Winter Garden. This essay examines Jacobsen’s long and difficult journey to obtain Gloria Victis, along with his motivation for acquiring a sculpture that, until World War I, was closely tied to France’s memory of the debacle of the Franco-Prussian War (1870–71). It argues that Jacobsen saw Gloria Victis not only as a major work of art and a signature piece in his museum but also as a monument in which French and Danish memories of recent military defeats were intertwined